The effect of online interruptions on the quality of cognitive performance. Issue 4 (November 2016) - Levy, Eilat Chen; Rafaeli, Sheizaf; Ariel, Yaron
Highlights: Online interruptions influence the amount of time spent on the cognitive task. The required compensation time is greater when interruptions conveyed by mobile phones than Internet application. Relative cognitive performance success is higher for those experienced poor interruption messages. Abstract: This paper examine the effect of the richness of online interruption messages on cognitive performance quality. An experimental research design utilized a computerized simulation game to measure participants' cognitive performance. Manipulation was achieved by exposing five groups ( N  = 120) to messages in 2 × 2 intervention design in mobile phones (SMS/MMS) and online application (text/banner). Results indicate a significant difference between experimental groups about the amount of time spent on the cognitive task. The analysis reveals a significant effect of the richness of the message on cognitive performance quality, and the main effect of medium. Nonetheless, the required compensation time was greater among the groups using mobile phones. Performing the task with a mobile phone required more time than with the Internet application. The mobile phone with MMS group had the longest recovery time of all the test groups. This study may provide some reasons to revisit and reconsider the popular expression, "a picture is worth a thousand words." Our findings run counter to Media Richness Theory, as we found that the degree of richness of the online interruption was not solely dictated by the properties of the conveying medium.